Membangun Resiliensi dari Bawah: Perempuan dengan Disabilitas dan Keadilan Iklim di Indonesia - Yogi Paramitha Dewi; Etheldreda E. L. T. Wongkar (Yayasan Jurnal Perempuan, 2022)
Socially, the impacts of climate change are unevenly distributed within the society. Those who have been marginalized, albeit their less contribution to climate change, have been the most vulnerable group suffered from those impacts due to their lack of access to resources and capacities to act. One segment within the group is women with disabilities. Although many policies dealing with adaptation and mitigation to climate change have been adopted by the government, specific interests of women with disabilities are not considered as a result from their lack of involvement and participation in the decision-making process. Nevertheless, women with disabilities have been undertaking voluntary initiatives to build resilience among themselves in dealing with the climate crisis. This article aims to examine the essence and significance of accommodating women with disabilities in formulating policies on climate change and to discuss how they exercise their agency to develop initiatives in responding to the problem. A combined conceptual framework from feminist environmentalism and climate justice is used here in addressing both issues